IMPROVING STUDENTS’ SKILL ON WRITING REPORT TEXT USING REFERENCES (A Report on Best Practice Conducted at Grade 9 of SMP Negeri 1 Dramaga Bogor) - Retnowati, Nanik (ENGLISH JOURNAL, 2017)
Improving students? writing skill is a prominent challenge for most of English teachers in secondary level of education. Writing activities are not always easy for most students due to many intertwining factors in writing process. Among the factors, students? mastery in grammar, vocabulary, and developing ideas are the most obstacles that the students encounter. Kinds of text may also be the source of difficulties. Some text may be related to students? daily activities so it is not too difficult for the students to write. For junior high school students, report text is not easy to write. Report text contains technical terms and accurate information, compared to composing other kinds of text, writing report text is more challenging since as an academic type of text, it requires more advanced knowledge both of grammar and vocabulary. The Students of SMP 1 Dramaga grade three found it difficult to compose a report text. The alternative way to solve the problem is by using references as pre writing activities. This best practice reports some important clues on how to use reference as a pre writing activity and students? improvement on three components of writing; i.e. grammar, vocabulary, and developing ideas.